Mosaic of Israel’s landscapes as an expression of geographical, cultural, and religious diversity - Dorot , Ruth (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Dorot Ruth, Mosaic of Israel’s landscapes as an expression of geographical, cultural, and religious diversity. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 87–113. ISSN 1731-450X. DOI 10.14746/i.2019.34.06. Israel is tiny in its dimensions, yet huge in the spectrum of its landscapes. It is ancient in its history, yet young as a state. In honor of the 70th independence day of the State of Israel, celebrated in 2018, this paper presents a mosaic of 12 landscape paintings, from the country’s most southern point to the most northern one, by Israeli artists who represent, in diverse styles, the state’s geographic and historic wealth in a visual-artistic sense.